2020
DOI: 10.1038/s41556-020-0501-4
|View full text |Cite
|
Sign up to set email alerts
|

Lis1 activates dynein motility by modulating its pairing with dynactin

Abstract: Lissencephaly-1 (Lis1) is a key cofactor for dynein-mediated intracellular transport towards the minus-ends of microtubules (MTs). It remains unclear whether Lis1 serves as an inhibitor or an activator of mammalian dynein motility. Here we use single-molecule imaging and optical trapping to show that Lis1 does not directly alter the stepping and force production of individual dynein motors assembled with dynactin and a cargo adaptor. Instead, Lis1 promotes the formation of an active complex with dynactin. Lis1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
179
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(211 citation statements)
references
References 67 publications
(124 reference statements)
30
179
2
Order By: Relevance
“…Importantly, a phi mutation that promotes open dynein (Zhang K. et al, 2017) bypasses the requirement for LIS1 to a significant extent (Qiu et al, 2019), suggesting that LIS1 is involved in promoting open dynein, thereby facilitating cargo adapter-mediated dynein activation (Qiu et al, 2019). This main conclusion agrees with three other recent studies (Elshenawy et al, 2020;Htet et al, 2020;Marzo et al, 2020), although LIS1 in A. nidulans does not seem to significantly affect the formation of the dynein-dynactin-C-Hook complex (Qiu et al, 2019), while LIS1 enhances the recruitment of the second dynein to the dynein-dynactin-BicD2N complexes in vitro (Elshenawy et al, 2020;Htet et al, 2020). Possibly, A. nidulans LIS1 still enhances the dynein-dynactin interaction as described in other systems (Dix et al, 2013;Wang et al, 2013), but this effect was not easily detected when the concentration of cytosolic cargo adapters is high enough.…”
Section: Lis1 Is a Positive Regulator For Dynein Activationsupporting
confidence: 92%
See 3 more Smart Citations
“…Importantly, a phi mutation that promotes open dynein (Zhang K. et al, 2017) bypasses the requirement for LIS1 to a significant extent (Qiu et al, 2019), suggesting that LIS1 is involved in promoting open dynein, thereby facilitating cargo adapter-mediated dynein activation (Qiu et al, 2019). This main conclusion agrees with three other recent studies (Elshenawy et al, 2020;Htet et al, 2020;Marzo et al, 2020), although LIS1 in A. nidulans does not seem to significantly affect the formation of the dynein-dynactin-C-Hook complex (Qiu et al, 2019), while LIS1 enhances the recruitment of the second dynein to the dynein-dynactin-BicD2N complexes in vitro (Elshenawy et al, 2020;Htet et al, 2020). Possibly, A. nidulans LIS1 still enhances the dynein-dynactin interaction as described in other systems (Dix et al, 2013;Wang et al, 2013), but this effect was not easily detected when the concentration of cytosolic cargo adapters is high enough.…”
Section: Lis1 Is a Positive Regulator For Dynein Activationsupporting
confidence: 92%
“…In contrast to dynactin that binds to the dynein tail (Karki and Holzbaur, 1995;Vaughan and Vallee, 1995;Chowdhury et al, 2015;Urnavicius et al, 2015), LIS1 binds directly to the dynein motor ring at AAA3/AAA4 as shown by cryo-EM studies (Huang et al, 2012;Toropova et al, 2014;Desantis et al, 2017;Htet et al, 2020). LIS1's binding to this site is not compatible with the autoinhibited phi conformation of dynein (Htet et al, 2020;Marzo et al, 2020), which supports a "check valve" (Markus et al, 2020) model of LIS1 mechanism of action: it stabilizes the open dynein conformation and prevents it from switching to the autoinhibited phi state, thereby facilitating cargo-adapter-mediated dynein activation (Qiu et al, 2019;Canty and Yildiz, 2020;Elshenawy et al, 2020;Htet et al, 2020;Markus et al, 2020;Marzo et al, 2020).…”
Section: Lis1 Is a Positive Regulator For Dynein Activationmentioning
confidence: 93%
See 2 more Smart Citations
“…However, Lis1 is best known as a key dynein motor regulator and is required for the efficient transport of many dynein‐associated cargoes within cells [105,110–112]. In vitro studies using purified recombinant protein, and more recently single‐molecule imaging and motility assays, have established that Lis1 promotes dynein activity and orchestrates dynein–dynactin transport machinery assembly [72,73,113–115]. Lis1 also interacts with the MT plus‐end‐binding protein CLIP‐170 (see below) [116,117] and with the dynein regulator Nde1 [109,118–121].…”
Section: Microtubule Basics Dynamic Instability and Partnersmentioning
confidence: 99%